2011
DOI: 10.1002/mabi.201100050
|View full text |Cite
|
Sign up to set email alerts
|

PAA‐Derived Gold Nanorods for Cellular Targeting and Photothermal Therapy

Abstract: A single-step LbL procedure to functionalize CTAB-capped GNRs via electrostatic self-assembly is reported. This approach allows for consistent biomolecule/GNR coupling using standard carboxyl-amine conjugation chemistry. The focus is on cancer-targeting biomolecule/GNR conjugates and selective photothermal destruction of cancer cells by GNR-mediated hyperthermia and NIR light. GNRs were conjugated to a single-chain antibody selective for colorectal carcinoma cells and used as probes to demonstrate photothermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…In one study, recombinant antibody fragments were constructed with different linkers to facilitate selective conjugation to primary amine or carboxylic acid groups on PEG using carbodiimide (EDC/NHS) chemistry [161].The mPEG-aldehyde was also randomly conjugated to (18)and the kinetic behaviour of the PEGylation reaction simulated mathematically [159], with even the non-site-specificconjugationsufficient to significantly increase the half-life of the scFv in the murine circulation.Polyacrylic acid (PAA)-coated gold nanorods have recently beenfunctionalized with scFvs specific for colorectal carcinoma cells using EDC/NHS chemistry. The resulting scFv-labelledPAA-gold nanorods exhibited selective targeting to and uptake in tumor cellsin tissue culture studies and could mediate selective photothermal killing of antigen-expressing cancer cellsin vitro [162].Similarly,poly(lactic-co-glycolic acid)(PLGA) loaded with histine deacetylase inhibitorwas covalently conjugated to scFvs targeting the CD7 surface marker on T lymphocytes. PLGA particles were first functionalized with ethylenediamine and then coupled with N-terminal-blocked scFvs by using EDC/NHS, following which the immunoparticles were able to successfully deliver their payload to human T cells [163].…”
Section: Amine Conjugationmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, recombinant antibody fragments were constructed with different linkers to facilitate selective conjugation to primary amine or carboxylic acid groups on PEG using carbodiimide (EDC/NHS) chemistry [161].The mPEG-aldehyde was also randomly conjugated to (18)and the kinetic behaviour of the PEGylation reaction simulated mathematically [159], with even the non-site-specificconjugationsufficient to significantly increase the half-life of the scFv in the murine circulation.Polyacrylic acid (PAA)-coated gold nanorods have recently beenfunctionalized with scFvs specific for colorectal carcinoma cells using EDC/NHS chemistry. The resulting scFv-labelledPAA-gold nanorods exhibited selective targeting to and uptake in tumor cellsin tissue culture studies and could mediate selective photothermal killing of antigen-expressing cancer cellsin vitro [162].Similarly,poly(lactic-co-glycolic acid)(PLGA) loaded with histine deacetylase inhibitorwas covalently conjugated to scFvs targeting the CD7 surface marker on T lymphocytes. PLGA particles were first functionalized with ethylenediamine and then coupled with N-terminal-blocked scFvs by using EDC/NHS, following which the immunoparticles were able to successfully deliver their payload to human T cells [163].…”
Section: Amine Conjugationmentioning
confidence: 99%
“…Procedures used to improve antibody fragment orientation and thus assay sensitivity, such as cysteine engineering and oxidation of site-specific glycan tags, have been demonstrated in our own group [63,212]and others. As a demonstration of the effectiveness oforiented conjugation, therefore, model Fab′ antibody fragments immobilized on 2-methacryloyloxyethyl phosphorylcholine (MPC) and glycidyl methacrylate (GMA) polymer and block copolymer brushes via a thiol-disulfide interchange reaction yielded high density, well-oriented immobilizedfragments for the development of highly sensitive biosensors [162]. Similarly, directed coupling of an anticreatine kinase antibody in a commercial EIA system resulted in a shorter assay time and improved assay performance over use ofthe uncomplexed antibody [213].…”
Section: In Vitro Applicationsmentioning
confidence: 99%
“…The SPR property offers a promising potential in improving a wide range of biomedical applications including colorimetric assay, 62 photoacoustic imaging 63 and photothermal therapy. 64 65 The SPR of Au nanostructures mainly depends on the shape and size, and is also influenced by the dielectric constant of the surrounding medium. The application of Au nanoparticles has also been recently extended to other imaging modalities such as optical coherence tomography (OCT), 66 surface enhanced Raman scattering imaging (SERS), 67 and fluorescence imaging.…”
Section: Gold Nanocrystalsmentioning
confidence: 99%
“…Scale bar is 50 μm. Reproduced with permission from reference [94] The many examples discussed above illustrate the exciting potential of using functionalized Au NMs for cancer diagnosis and therapy, by coupling biomedical imaging with photothermal therapy to provide a noninvasive alternative to surgery for cancer treatments.…”
Section: Imaging and Phototherapymentioning
confidence: 99%
“…Considering biological applications, the interactions of Au NMs with cells have been explored [9,13,93,94]. Results showed that Au NMs absorb proteins from fetal bovine serum quickly after they are incubated with cell culture medium, forming a protein-nanoparticle corona, which can be internalized by cells through receptor or non-receptor mediated endocytosis and then translocated to endosomes or lysosomes in most cases.…”
Section: Potential Risk Assessmentmentioning
confidence: 99%